HUMAN RESOURCE MANAGEMENT IN THE EDUCATION SYSTEM - Muhammad Ihsan Dacholfany; Wulandari; Marzuki (International Journal of Teaching and Learning, 2025)
Human resource management (HRM) in the education sector is an important aspect in ensuring the delivery of high-quality education. The research method in this study uses the literature research method. The results showed that the keys to successful HRM include effective recruitment, continuous professional development, motivation and maintaining a positive work climate. It was found that institutions that implemented a systematic approach to career development had higher performing educators and students with better learning outcomes. Stakeholder engagement and the application of the latest educational technology also contribute positively to efficient HRM